2014
DOI: 10.1088/0953-8984/26/50/505901
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically induced absorption in detuned stub waveguides: a simple analytical and experimental model

Abstract: We give an analytical and experimental demonstration of a classical analogue of the electromagnetic induced absorption (EIA) in a simple photonic device consisting of two stubs of lengths d1 and d2 grafted at the same site along a waveguide. By detuning the lengths of the two stubs (i.e. δ = d(2) - d(1)) we show that: (i) the amplitudes of the electromagnetic waves in the two stubs can be written following the two resonators model where each stub plays the role of a radiative resonator with low Q factor. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 59 publications
(96 reference statements)
1
30
0
Order By: Relevance
“…The principal advantage of the electromagnetic SWGs structure presented in this paper is linked to the existence of several transmission peaks of the defects modes depending on the different resonators defects lengths, their numbers, and their positions. The obtained results demonstrate that our proposed filter based on multi-defects modes has a very important transmission coefficient and very high quality factor compared to no-periodic acoustic or photonic waveguides structure system [33,34]. We believe that this paper brings a new piece of work in the field of electromagnetic wave transport in 1D waveguide structures containing different types of metamaterials [35][36][37][38][39][40].…”
Section: Numerical Results and Discussionmentioning
confidence: 63%
“…The principal advantage of the electromagnetic SWGs structure presented in this paper is linked to the existence of several transmission peaks of the defects modes depending on the different resonators defects lengths, their numbers, and their positions. The obtained results demonstrate that our proposed filter based on multi-defects modes has a very important transmission coefficient and very high quality factor compared to no-periodic acoustic or photonic waveguides structure system [33,34]. We believe that this paper brings a new piece of work in the field of electromagnetic wave transport in 1D waveguide structures containing different types of metamaterials [35][36][37][38][39][40].…”
Section: Numerical Results and Discussionmentioning
confidence: 63%
“…14 Hz is the decay rate due to losses of the HRs [23]. Ignoring the losses, it has been shown that, for small values of the detuning parameter, the transmission coefficient presents an EIT-like mode with unity transmission at f 0 = (f HR 2 +f HR 1 )/2 [2,5,9,24,25]. The lossless transmission coefficient in the complex frequency plane is displayed in Fig.…”
mentioning
confidence: 99%
“…In this section we review the main features of PA through the interplay of the inherent losses and transparent modes [67][68][69][70][71] with high Q factor as shown in [42]. These modes are generated in a two-port one-dimensional waveguide which is side-loaded by isolated resonators with moderate Q factor.…”
Section: Perfect Absorption In Two Port Systemsmentioning
confidence: 99%